Laboratory Diagnostic and Monitoring at Early Stages of SARS-CoV-2 Infection: Case Report and Literature Review - Adhi Kristianto Sugianli; Dewi Kartika Turbawaty; Ida Parwati (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2022)
COVID-19 is a new respiratory disease caused by severe acute respiratory syndrome Coronavirus type 2 (SARS-CoV-2) and became a pandemic in early 2020. Since the clinical presentation of this viral infection can mimic other types of viral infection (e.g., dengue, influenza, and another respiratory disease), the laboratory approach becomes essential, particularly at the early stages of infection. This case-literature review approach described an outpatient case of a 39-year-old male patient with mild-to-moderate COVID-19 who recovered after 49 days of self-quarantine. Lymphopenia and mild thrombocytopenia can be used as early screening for COVID-19 at the early stages of infection and mainly occur in outpatient settings. Meanwhile, Neutrophil-to-Lymphocyte Count Ratio (NLCR), C-Reactive Protein (CRP), and Liver Function Test (LFT) can be used for severity prediction and/or follow-up the outcome of the infected patient. Therefore, the integrated clinical-laboratory finding at the early stages of infection is vital to provide better and effective patient management.